Using visual-based social norm methods to understand distance-related human–wildlife interactions. Issue 2 (4th March 2018) - Miller, Zachary D.; Freimund, Wayne
ABSTRACT: Distance-related human–wildlife interactions are a challenge in diverse settings across the globe. However, few methodological approaches have been proposed to explore the issue of distance in human dimensions research. Drawing from previous research related to crowding, noise pollution, and other visitor experience concepts, this methodological article describes a novel visual-based social norm method for evaluating distance-related human–wildlife interactions. We discuss the process of constructing the tools, the field testing of the techniques in Yellowstone National Park, and reflect on the methodological approach. From these methods, practitioners can gain information about distance thresholds of visitors in relation to wildlife viewing and potentially help identify deviant groups of visitors. Future research directions include pre-post research designs, controlled experiments, and belief evaluations for improving communications.